Chromium adsorption from petroleum refinery wastewater using biocomposites - Matthew C. Menkiti; Chukwunonso O. Aniagor; Chioma M. Onuzulike; Marcel I. Ejimofor; Somtochukwu S. Okonkwo (Results in Surfaces and Interfaces, 2022)
In this study, microbially synthesized biosurfactants were immobilized on mesoporous activated carbon and the biocomposites were further utilized for chromium removal from petroleum refinery wastewater. Due to the acidic and lactone rings on the E. coli biosurfactant, which confers improved hydrophilicity, the activated carbon functionalized with E-coli biosurfactant (EB-Zn/AC) depicted better chromium adsorption than the sophorolipid functionalized activated carbon (SB-Zn/AC). Hence, at 240 min, pH 8.0 and biocomposite concentration of 6.0 g/L, a maximum adsorption efficiency of 99.60% and 53.98 was recorded for EB-Zn/AC and SB-Zn/AC, respectively. The isotherm and kinetic data correlated best with Freundlich and pseudo-second-order models, respectively for both biocomposites, with their coefficient of determination (R2) value greater than 0.9 in all cases. Thermodynamic parameters show that the process was feasible and spontaneous. The post adsorption water sample characterization result shows that the chromium ion concentration was brought within EPA (Environmental Protection Agency) wastewater discharge standard.